Towards a framework for early cost estimation based on process complexity index for machined components - Wahyu Purnawirawan; Jos Istiyanto; Gerry Liston Putra; Hendri DS Budiono (Prosiding SNTTM, 2025)
Preliminary cost estimating is a pivotal element in ascertaining the competitive viability of manufacturing sectors. The initial design phase, when comprehensive information on methods and standards remains significantly constrained, allocates approximately 70–80% of overall manufacturing expenses. This paper presents a conceptual framework for preliminary cost assessment grounded in process complexity indices, specifically targeting machined components. The framework is constructed using a modular approach comprising three primary components: CAD/CAM system, analysis module, and reference module. The CAD/CAM system module extracts geometric data from CAD models, classifies manufacturing aspects, and delineates product complexity attributes. The Analyzing Module encompasses manufacturability assessment, production duration estimation, cost calculation, and evaluations of product and process complexity. The Reference Module offers auxiliary databases, encompassing machine cost rates, labor expenses, tool specs, manufacturing process repositories, and complexity databases. The integration of these three modules facilitates more precise cost estimation, especially in the absence of specific production information. A literature analysis demonstrates that feature recognition methods—geometry-based, rule-based, graph-based, and hybrid—can be integrated to enhance this system. The suggested framework aims to enhance the dependability of early design-stage forecasts by including complexity traits into cost estimates, hence establishing a basis for the creation of more adaptive and automated cost estimation systems suited to contemporary manufacturing requirements.